Utilization-Focused Evaluation (U-FE) Checklist - Patton, Michael Quinn (The Evaluation Center, 2013)
Utilization-Focused Evaluation begins with the premise that evaluation s should be judged by their utility and actual use; therefore, evaluat ors should facilitate the evaluation process and design any evaluation with careful consideration of how everything that is done, from begin ning to end, will affect use. Use concerns how real people in the real world apply evaluation findings and experience and learn from the eva luation process. The checklist is based on Essentials of Utilization-F ocused Evaluation (Patton, 2012, Sage Publications). All references in the checklist to exhibits and menus refer to this book. Step 1 Assess and build program and organizational readiness for utilization-focuse d evaluation. Step 2 Assess and enhance evaluator readiness and compet ence to undertake a utilizationfocused evaluation. Step 3 Identify, or ganize, and engage primary intended users. Step 4 Conduct situation an alysis with primary intended users Step 5 Identify primary intended us es by establishing the evaluation’s priority purposes. Step 6 Consider and build in process uses if appropriate. Step 7 Focus priority evalu ation questions. Step 8 Check that fundamental areas for evaluation in quiry are being adequately addressed. Step 9 Determine what interventi on model or theory of change is being evaluated. Step 10 Negotiate app ropriate methods to generate credible findings and support intended us e by intended users. Step 11 Make sure intended users understand poten tial controversies about methods and their implications. Step 12 Simul ate use of findings. Step 13 Gather data with ongoing attention to use . Step 14 Organize and present the data for use by primary intended us ers. Step 15 Prepare an evaluation report to facilitate use and dissem inate significant findings to expand influence. Step 16 Follow up with primary intended users to facilitate and enhance use. Step 17 Metaeva luation of use: Be accountable, learn, and improve